2002
DOI: 10.1105/tpc.000620
|View full text |Cite
|
Sign up to set email alerts
|

The Destination for Single-Pass Membrane Proteins Is Influenced Markedly by the Length of the Hydrophobic Domain

Abstract: The tonoplast was proposed as a default destination of membrane-bound proteins without specific targeting signals. To investigate the nature of this targeting, we created type I fusion proteins with green fluorescent protein followed by the transmembrane domain of the human lysosomal protein LAMP1. We varied the length of the transmembrane domain from 23 to either 20 or 17 amino acids by deletion within the hydrophobic domain. The resulting chimeras, called TM23, TM20, and TM17, were expressed either transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
255
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(270 citation statements)
references
References 48 publications
13
255
0
1
Order By: Relevance
“…In studies in yeast (see Rayner and Pelham, 1997) and more recently in plants (Brandizzi et al, 2002), the length of the TM helix has been shown to play a major role in protein sorting because the helix needs to be at least 23 amino acids to span and to permit sorting to the PM. The predicted TM helices of MtLecRK1;1 and MtLecRK7;2 are 23 amino acids in length, thus fulfilling this sorting requirement.…”
Section: Discussionmentioning
confidence: 99%
“…In studies in yeast (see Rayner and Pelham, 1997) and more recently in plants (Brandizzi et al, 2002), the length of the TM helix has been shown to play a major role in protein sorting because the helix needs to be at least 23 amino acids to span and to permit sorting to the PM. The predicted TM helices of MtLecRK1;1 and MtLecRK7;2 are 23 amino acids in length, thus fulfilling this sorting requirement.…”
Section: Discussionmentioning
confidence: 99%
“…As a control for the efficiency of the BFA treatment, we analyzed the BFAsensitive localization of TM23:GFP, a modified GFP containing a transmembrane domain (Brandizzi et al, 2002).…”
Section: Bfa and Sar1 Do Not Affect Acylation And Plasma Membrane Tarmentioning
confidence: 99%
“…Of particular use for our present investigation is TMcCCASP, a chimeric type I protein (Hanton et al, 2005b) consisting of a form of GFP carrying a signal peptide for entry into the ER and an N-glycosylation site (Batoko et al, 2000) fused to a 17-amino acid transmembrane domain, the short length of which restricts type I proteins to the ER (Brandizzi et al, 2002a). Adjacent to the transmembrane domain are 78 amino acids of the cytosolic domain of CASP (Hanton et al, 2005b;Renna et al, 2005), containing a functional diacidic ER export motif that is dominant over the properties of the transmembrane domain and permits Figure 1.…”
Section: Eres Formation and Copii Recruitment To Eres Are Signal Depementioning
confidence: 99%